Mother, sister, daughter Nepal's press on women. - United Nations Development Fund for Women (Kathmandu Sancharika Samuha, 2002)
Contributed articles on state of Women in Nepal published earlier as features in Nepali press.
"The publication of this book was made possible through the support of UNIFEM."--T. p. verso.
Keywords: Women -- Press coverage -- Nepal; Women -- Nepal -- Social conditions